EFFECT OF REPLACEMENT OF COMMERCIAL RATION WITH FERMENTED GREEN BEAN SPROUT WASTE FLOUR ON THE APPEARANCE OF BALI DUCKS - N. M. L. E., Witarja; Siti, N W.; Wibawa, A. A. P. P. (Jurnal Peternakan Tropika; Vol 8 No 2 (2020): Vol. 8 No. 2 Tahun 2020; Mei - Agustus, 2020)
This study aims to determine the effect of replacing commercial rations with fermented mung bean sprouts flour on the appearance of male Bali ducks aged 0-8 weeks. The study used a Completely Randomized Design (CRD) with three treatments, each treatment using five replications and each repetition used three male Bali ducks with a duck weight of 43,8 ± 0,96g. The treatment given is; P0 (100% commercial ration), P1 (replacement of 12,5% ??commercial ration with fermented mung bean sprout waste flour) and P2 (replacement of 25% commercial ration with fermented mung bean sprout waste flour). The variables observed in this study were initial body weight, feed consumption, drinking water consumption, final body weight, weight gain and Feed Convertion Ratio. The results showed that the replacement of 12,5% ??and 25% commercial rations with fermented mung bean sprouts flour had no significant effect (P>0,05) on ration consumption, drinking water consumption, final body weight, weight gain and FCR. Based on the results of the study it can be concluded that the replacement of up to 25% of the commercial ration with fermented mung bean sprouts did not lose the superiority of male Bali ducks.   Keywords : Bali ducks, waste, green beans, commercial rations, fermentation